Thermal curing of composites based epoxy - Lia Wijayanti Pratomo. (2010)
Thermal curing has been around for many years and yet still dominating in the marketplace because of its applicability to many industrial purposes such as coatings, composites and adhesives. The easy and effective curing of the resin and hardener makes this technique of curing interesting and viable in the area of industry. This project investigated the cure kinetics of Epolam 5015 system (see structure p.13) using differential scanning calorimetry (DSC) under non-isothermal and isothermal methods. Furthermore, the degree of curing (conversion), conversion rate, enthalpy of curing and glass transition temperature (Tg) was measured to calculate the kinetic parameters (i.e. activation energy and pre-exponential factor) of the system. Variation of epoxy and hardener ratio of Epolam 5015 system (see structure p.13) was found to have a significant effect on the cure kinetic parameters. It was found that this optimum system corresponds to 100/30 wt%/wt% ratio of resin and hardener, respectively.